Women's experiences of a telemedicine abortion service (up to 12 weeks) implemented during the coronavirus (COVID‐19) pandemic: a qualitative evaluation. (27th July 2021) - Boydell, N; Reynolds‐Wright, JJ; Cameron, ST; Harden, J
Abstract : Objective: To explore the experiences of women in Scotland who accessed medical abortion at home up to 12 weeks' gestation, delivered via a telemedicine abortion service implemented in response to the coronavirus (COVID‐19) pandemic, to identify areas for improvement and inform service provision. Design: Qualitative interview study. Setting: Abortion service in one National Health Service health board in Scotland. Population or sample: Twenty women who accessed telemedicine abortion services and self‐administered mifepristone and misoprostol at home up to 12 weeks' gestation. Methods: Thematic analysis of semi‐structured qualitative interviews, informed by the Framework analytic approach. Main outcome measures: Women's experiences of accessing telemedicine for medical abortion at home, specifically: acceptability of the telephone consultation and remote support; views on no pre‐abortion ultrasound scan; and self‐administration of abortion medications at home. Results: Novel study findings were three‐fold: (1) participants valued the option of accessing abortion care via telemedicine and emphasised the benefits of providing a choice of telephone and in‐person consultation to suit those with different life circumstances; (2) the quality of abortion care was enhanced by the telemedicine service in relation to access, comfort and flexibility, and ongoing telephone support; (3) participants described being comfortable with, and in some cases a preference for, not having an ultrasound scan. Conclusions: This research demonstrates support for the continuation of telemedicine abortion services beyond the temporary arrangements in place during COVID‐19, and lends weight to the argument that offering the option of telemedicine abortion care can enable women to access this essential health service. Tweetable abstract: #Telemedicine provision of medical #abortion at home up to 12 weeks' gestation is acceptable and highly valued by #women #Research #SRHR @nbw80 @doctorjjrw @jeniharden @cameronsharon @mrc_crh @edinuniusher. Tweetable abstract: #Telemedicine provision of medical #abortion at home up to 12 weeks' gestation is acceptable and highly valued by #women #Research #SRHR @nbw80 @doctorjjrw @jeniharden @cameronsharon @mrc_crh @edinuniusher. This article includes Author Insights, a video abstract available at: https://vimeo.com/bjog/authorinsights16813